2018
DOI: 10.1007/s10706-018-0511-1
|View full text |Cite
|
Sign up to set email alerts
|

Settlement Prediction of Model Piles Embedded in Sandy Soil Using the Levenberg–Marquardt (LM) Training Algorithm

Abstract: This investigation aimed to examine the load carrying capacity of model piles embedded in sand soil and to develop a predictive model to simulate pile settlement using a new artificial neural network (ANN) approach. A series of experimental pile load tests were carried out on model concrete piles, comprised of three piles with slenderness ratios of 12, 17 and 25. This was to provide an initial dataset to establish the ANN model, in attempt at making current, in situ pile-load test methods unnecessary. Evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Here, ∆x t , H e , and g t represent the updated value of the weight, Hessian matrix, and current gradient, respectively. H e and g t can be obtained from Equations (11) and (12), where J and r(x) represent the Jacobian matrix and the error, respectively:…”
Section: Lm Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, ∆x t , H e , and g t represent the updated value of the weight, Hessian matrix, and current gradient, respectively. H e and g t can be obtained from Equations (11) and (12), where J and r(x) represent the Jacobian matrix and the error, respectively:…”
Section: Lm Algorithmmentioning
confidence: 99%
“…In recent years, the LM algorithm has been favored by domestic and overseas scholars [9][10][11][12]. It is a classical nonlinear numerical optimization algorithm that combines the advantages of the gradient descent method and the Gauss-Newton method.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of the LM training algorithm has recently been underlined as an efficient prediction tool in many engineering sectors and is now gaining growing attention in engineering research (Deo and Şahin, 2015;Juncai et al, 2015;Jebur et al, 2018b). These technical papers have reported the outstanding performance of the LM algorithm over the classical artificial neural networks methods.…”
Section: Implementation and Mathematical Background Of The Lm Algorithmmentioning
confidence: 99%
“…Unlike conventional training methods, the trained LM has several distinctive merits in that it is self-tuning training (doesn't require user dependent parameters after each application), it is 10 to 100 times faster without being trapped in local minima, less vulnerable to overfitting issues, has the ability to determine the optimum solution during the learning process, and it is extremely recommended as the first choice of supervised algorithm. (Abdellatif, 2013;Alrashydah and Abo-Qudais, 2018;Jebur et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that for a pile having length to diameter ratio 40 and constructed in dry dense sand, the bending moment and deformation increase when input motion is severe. Jebur et al (2018) develop a predictive model to determine pile settlement using a novel artificial intelligence method considering Levenberg-Marquardt MATLAB algorithms. Based on the statistical analysis, they found that pile length, applied load, pile flexural rigidity, pile aspect ratio and sand-pile friction angle have significant influence in pile settlement.…”
Section: Introductionmentioning
confidence: 99%